THE INFLUENCES OF CRYPTOCURRENCY ON ECONOMIC GROWTH: CASE STUDY OF BITCOIN IN 5 ASIAN COUNTRIES 2011-2016 PERIOD - Utomo, Grace Oktavia Tanti (Jurnal Ilmiah Mahasiswa FEB, 2018)
Cryptocurrency is a form of money that is secured by cryptography, a technology that will keep safe any information from third parties, to pacify the transactions and to control its value over time. Cryptocurrency has no organization or institution who has authority to control it, which makes some people think that it is not safe. Many research has talking about cryptocurrency in its technological side. However, no study has ever been correlating this topic with economic growth. Using panel data regression, this thesis correlating BTC, as the most known and expedienced type of cryptocurrency with GDP as the variable that represent economic growth. It also has 3 other variables as the control variable that will make sure the result to be unbiassed. Those are capital (K), labor (L), and Technology (A), as in the Solowâ€™s growth theory which reviewing growth through its supply side, the input production function. The sample are taken from 5 Asian countries with the highest number of Bitcoin usages (Japan, China, India, Singapore, Indonesia), with period that started from 2011 to 2016.KEYWORDS: Cryptocurrency, economic growth, solow growth model, bitcoin.Â